The Effectiveness of Quillbot's Grammar Checker on Students’ Writing Skills - Altalarik, Agel; Misrita; Ristati (PROJECT (Professional Journal of English Education), 2025)
The research aims to investigate the effect of QuillBot’s grammar checker on students’ writing skills of descriptive text at SMAN 1 Palangka Raya. The motivation to conduct this research is to explore the effectiveness of the QuillBot’s grammar checker at SMAN 1 Palangka Raya, especially in enhancing students’ writing skills in writing descriptive text. The research employed quantitative research with true experimental randomization subject post-test only control group design. The subject of the research were 44 students of X-I as the experimental group and 44 students of X-J as the control group at SMAN 1 Palangka Raya. The data of the research contains the scores of students writing test in writing descriptive text that collected during both post-test in the control and experimental groups. The result showed the mean score of 74.07 in control group and 82.61 in experimental group in the passing grade of 75.00, indicating a better achievement in the experimental group which applied the QuillBot’s grammar checker. The result of hypothesis showed sig. (2-tailed) of 0.000 which lower than probability value of 0.05, indicating Ho is rejected, or Ha is accepted. This implies that there is an effect of using the “QuillBot’s grammar checker” on students’ achievement in writing descriptive text by the tenth-grade students at SMAN 1 Palangka Raya.